Surface-associated lipid droplets: an intermediate site for lipid transport in human adipocytes? - Morén, Björn (Adipocyte, 2020)
Adipose tissue plays a major role in regulating whole-body energy metabolism. While the biochemical processes regulating storage and release of excess energy are well known, the temporal organization of these events is much less defined. In this study, we have characterized the presence of small surface-associated lipid droplets, distinct from the central droplet, in primary human adipocytes. Based on microscopy analyses, we illustrate the distribution of mitochondria, endoplasmic reticulum and lysosomes in the vicinity of these specialized lipid droplets. Ultrastructure analysis confirmed the presence of small droplets in intact adipose tissue. Further, CIDEC, known to bind and regulate lipid droplet expansion, clearly localized at these lipid droplets. Neither acute or prolonged stimulation with insulin or isoprenaline, or pharmacologic intervention to suppress lipid flux, affected the presence of these lipid droplets. Still, phosphorylated perilipin and hormone-sensitive lipase accumulated at these droplets following adrenergic stimuli, which supports metabolic activity at these locations. Altogether, we propose these lipid droplet clusters represent an intermediate site involved in lipid transport in primary adipocytes.